Layer-controlled epitaxy of 2D semiconductors: bridging nanoscale phenomena to wafer-scale uniformity. (17th August 2018) - Chiappe, Daniele; Ludwig, Jonathan; Leonhardt, Alessandra; El Kazzi, Salim; Nalin Mehta, Ankit; Nuytten, Thomas; Celano, Umberto; Sutar, Surajit; Pourtois, Geoffrey; Caymax, Matty; Paredis, Kristof; Vandervorst, Wilfried; et al.
Abstract: The rapid cadence of MOSFET scaling is stimulating the development of new technologies and accelerating the introduction of new semiconducting materials as silicon alternative. In this context, 2D materials with a unique layered structure have attracted tremendous interest in recent years, mainly motivated by their ultra-thin body nature and unique optoelectronic and mechanical properties. The development of scalable synthesis techniques is obviously a fundamental step towards the development of a manufacturable technology. Metal-organic chemical vapor deposition has recently been used for the synthesis of large area TMDs, however, an important milestone still needs to be achieved: the ability to precisely control the number of layers and surface uniformity at the nano-to micro-length scale to obtain an atomically flat, self-passivated surface. In this work, we explore various fundamental aspects involved in the chemical vapor deposition process and we provide important insights on the layer-dependence of epitaxial MoS2 film's structural properties. Based on these observations, we propose an original method to achieve a layer-controlled epitaxy of wafer-scale TMDs.